Research Opportunity Analysis in The Implementation of Scientific Literacy with Learning Media: Systematic Literature Network Analysis - Olyivia Retdwina Rusma; Muslim Muslim; Lilit Rusyati; Adlina Eugenia Fatimah Ghaisani (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2025)
This study aims to show research trend data related to learning media related to science literacy. This research uses the Systematic Literature Network Analysis (SLNA) method. The data used in this study is a collection of several articles based on Scopus data taken using the Publish or Perish (PoP) search. Based on this application, 6283 articles were obtained. Then, by filtering through the titles, 83 articles that were suitable for analysis were obtained. The analysis results show that topics often discussed in science literacy learning media are assessment, evaluation, technology, computers, the web, digital games, and many others. Based on this analysis, assessment is one of the future research directions related to science media literacy. Using the media in science literacy facilitates assessment, saves time, and presents visual phenomena that enrich students' understanding. Media can stimulate students to complete more concrete and real information to get clear and engaging experiences and improve scientific literacy related to scientific issues in the surrounding environment. With technologies such as computers, the web, and digital games, learning becomes more interactive, opening up great opportunities for scientific literacy for future in-depth research.